Transformation ratio at wakefield acceleration in dielectric resonator - Maslov, V.I.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2014)
The expressions for the wakefield have been derived and it has been shown that the transformation ratio in the dielectric resonator is significantly higher than the transformation ratio in the case of waveguide at large number of injected trains of identical bunches.